2012
DOI: 10.1111/j.1540-8159.2012.03345.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Left Ventricular (LV) Remodeling on Ventricular Arrhythmia in Cardiac Resynchronization Therapy (CRT‐D) Patients (Antiarrhythmic Effect of CRT)

Abstract: Reverse remodeling associated with CRT implantation can result in decreased frequency of ventricular arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 24 publications
2
13
0
1
Order By: Relevance
“…The results indicate a close correlation between LV function improvement and lower risks of appropriate ICD therapy and the composite endpoint of all‐cause mortality or heart transplant in patients with HFrEF who underwent ICD implantation as a secondary prevention. These results are consistent with those of previous studies that reported LV function improvement in association with favorable outcomes after ICD implantation for primary prevention, CRT‐D upgrade, or new CRT‐D implantation …”
Section: Discussionsupporting
confidence: 93%
“…The results indicate a close correlation between LV function improvement and lower risks of appropriate ICD therapy and the composite endpoint of all‐cause mortality or heart transplant in patients with HFrEF who underwent ICD implantation as a secondary prevention. These results are consistent with those of previous studies that reported LV function improvement in association with favorable outcomes after ICD implantation for primary prevention, CRT‐D upgrade, or new CRT‐D implantation …”
Section: Discussionsupporting
confidence: 93%
“…According to previous reports, reverse remodeling by CRT was associated with a significant reduction in the risk of subsequent ventricular arrhythmia. [29][30][31] This could be a factor in the different VT/VF incidence rate.…”
Section: -6mentioning
confidence: 99%
“…19 However, large clinical studies have suggested that CRT-P could contribute by itself to a reduction in mortality by decreasing the incidence of lethal ventricular arrhythmias, 20 supported by the fact that biventricular cardiac pacing produces reverse remodeling with a favorable impact on outcome and can reduce frequency of ventricular arrhythmias. [21][22][23] Concerning reverse remodeling, the process induced by CRT results in both mechanical and electrical stability of the left ventricle, leading to a lower risk of both heart failure (HF) and arrhythmic events; as shown by Barsheshet et al, 24 a favorable [>25% reduction in left ventricular end-systolic volume (LVESV)] echocardiographic response to CRT-D is associated with a significant 55% reduction in the risk of ventricular arrhythmias compared with ICD-only therapy.…”
Section: Discussionmentioning
confidence: 99%